Discovery of a novel species, Theileria haneyi n. sp., infective to equids, highlights exceptional genomic diversity within the genus Theileria: implications for apicomplexan parasite surveillance. Issue 9 (August 2018) - Knowles, Donald P.; Kappmeyer, Lowell S.; Haney, Darrell; Herndon, David R.; Fry, Lindsay M.; Munro, James B.; Sears, Kelly; Ueti, Massaro W.; Wise, Lauren N.; Silva, Marta; Schneider, David A.; Grause, Juanita; et al.
Graphical abstract: Highlights: Genomic diversity between Theileria equi and Theileria haneyi is greater than Theileria parva and Theileria annulata. Divergence time between T. equi and T. haneyi is greater than 33 million years. Genomic diversity between T. equi and T. haneyi is not reflected in differences in pathogenesis. The Equi merozoite antigen superfamily, present in T. equi, is also present in T. haneyi. Diversity of Theileria in equids is exceptional and presents consequences for parasite surveillance. Abstract: A novel apicomplexan parasite was serendipitously discovered in horses at the United States – Mexico border. Phylogenetic analysis based on 18S rDNA showed the erythrocyte-infective parasite to be related to, but distinct from, Theileria spp. in Africa, the most similar taxa being Theileria spp . from waterbuck and mountain zebra. The degree of sequence variability observed at the 18S rDNA locus also suggests the likely existence of additional cryptic species. Among described species, the genome of this novel equid Theileria parasite is most similar to that of Theileria equi, also a pathogen of horses. The estimated divergence time between the new Theileria sp. and T. equi, based on genomic sequence data, is greater than 33 million years. Average protein sequence divergence between them, at 23%, is greater than that of Theileria parva and Theileria annulata proteins, which is 18%. The latter two represent highly virulent Theileria spp. of domestic cattle, as well as of African and Asian wild buffalo, respectively, which differ markedly in pathology, host cell tropism, tick vector and geographical distribution. The extent of genome-wide sequence divergence, as well as significant morphological differences, relative to T. equi justify the classification of Theileria sp. as a new taxon. Despite the overall genomic divergence, the nine member equi merozoite antigen (EMA) superfamily, previously found as a multigene family only in T. equi, is also present in the novel parasite. Practically, significant sequence divergence in antigenic loci resulted in this undescribed Theileria sp. not being detectable using currently available diagnostic tests. Discovery of this novel species infective to equids highlights exceptional diversity within the genus Theileria, a finding with serious implications for apicomplexan parasite surveillance.